Functional roles and clinical values of insulin-like growth factor-binding protein-5 in different types of cancers - GÜLLÜ AMURAN, GÖKÇE; AKKİPRİK, MUSTAFA (SUN YAT SEN UNIV MED SCI WHO, 2012)
Insulin-like growth factor-binding proteins (IGFBPs) are critical regulators of the mitogenic activity of insulin-like growth factors (IGFs). IGFBP5, one of these IGFBPs, has special structural features, including a nuclear transport domain, heparin-binding motif, and IGF/extracellular matrix/acid-labile subunit-binding sites. Furthermore, IGFBP5 has several functional effects on carcinogenesis and even normal cell processes, such as cell growth, death, motility, and tissue remodeling. These biological effects are sometimes related with IGF (IGF-dependent effects) and sometimes not (IGF-independent effects). The functional role of IGFBP5 is most likely determined in a cell-type and tissue-type specific manner but also depends on cell context, especially in terms of the diversity of interacting proteins and the potential for nuclear localization. Clinical findings show that IGFBP5 has the potential to be a useful clinical biomarker for predicting response to therapy and clinical outcome of cancer patients. In this review, we summarize the functional diversity and clinical importance of IGFBP5 in different types of cancers.
Keywords: Cancer; IGFBP5; structure; function; proteolysis; clinical importance